Double-edged sword effect of packaging: Antecedents and consumer consequences of a company's green packaging design. (20th June 2023) - Chang, Tai-Wei
Abstract: This study aimed to investigate the relationship between green production and sustainable consumption, with a focus on green packaging design and the integration of stakeholder theory and expected-value theory. Two studies were conducted to address the research gap from the perspectives of both enterprises and consumers. Study 1 highlighted the importance of employees' degree of psychological ownership of green products for improving green packaging design, while study 2 explored the dual role of green packaging design in influencing consumers' green purchasing behavior through both green skepticism and green perceived value. The findings have practical and theoretical implications for the promotion of green production and sustainable consumption.